2008
DOI: 10.1002/chem.200800421
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Catalyzed Cascade Reactions of Diarylvinylidenecyclopropanes and 1,1,3‐Triarylprop‐2‐yn‐1‐ols or Their Methyl Ethers

Abstract: The reactions of vinylidenecyclopropanes 1 with 1,1,3-triarylprop-2-yn-1-ols or their methyl ethers 2 in the presence of a Lewis acid selectively produce 4-dihydro-1H-cyclopenta[b]naphthalene derivatives 3 or 1,2,3,8-tetrahydrocyclopenta[a]indene derivatives 4 depending on the substituents on the cyclopropane. Good to high yields are obtained under mild conditions. A plausible cascade Meyer-Schuster rearrangement and Friedel-Crafts reaction mechanism has been proposed. Moreover, novel functionalized methylenec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In our previous work, we reported that the reaction of VDCPs with 1,1,3‐triarylprop‐2‐yn‐1‐ols or their methyl ethers selectively produced 4‐dihydro‐1 H ‐cyclopenta[ b ]naphthalene derivatives or 1,2,3,8‐tetrahydrocyclopenta[ a ]indene derivatives in the presence of Lewis acid, depending on the substituents at the cyclopropane 22. However, the intramolecular reaction of VDCPs with propargyl alcohol has not been explored to date.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we reported that the reaction of VDCPs with 1,1,3‐triarylprop‐2‐yn‐1‐ols or their methyl ethers selectively produced 4‐dihydro‐1 H ‐cyclopenta[ b ]naphthalene derivatives or 1,2,3,8‐tetrahydrocyclopenta[ a ]indene derivatives in the presence of Lewis acid, depending on the substituents at the cyclopropane 22. However, the intramolecular reaction of VDCPs with propargyl alcohol has not been explored to date.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the reactions of acetylb romide and FeBr 3 with other acetal-VDCPs 1 were then carriedo ut to define the Chem.E ur.J.2015, 21,15964 -15969 www.chemeurj.org generality of this protocol. Similarly,w hen using acetal-VDCPs 1b-j as the substrates, the desired brominated products 3b-j were obtained in moderate to good yields (50-68 %; Table 2, entries [14][15][16][17][18][19][20][21][22]. Next, the carbon chain length of acetal-VDCPs was extended and different acetals were synthesized to expand the substrate scope and conductf urthert ransformation of the products (Table 3).…”
mentioning
confidence: 99%
See 2 more Smart Citations